(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The existence of the oil resource caused a shift in the economic, political and social history of Iraq, and included the impact on the nature of social relations in Iraqi society, as this resource constitutes the basis for public revenues in the general budget, but the policies and attempts at economic diversification that were pursued brought results that do not rise to the required level, and that Economic unilateralism, about which a lot of intellectual controversy was raised, has become more clear and mature in the current era. The requirements for reconstruction and debt repayment have become a reason for achieving relative separation between revenues and achieving well-being, and reflect the misconduct in the management of oil revenues within the traditional budget, which means a decline in economic performance rates and achievement rates.It is clear from the foregoing that the research sheds light on the means of managing oil revenues, potential solutions on the ground, and opportunities for achieving economic development in the oil sector.